Understanding the Karoo dolerite systems using geological and geophysical methods around Beaufort West, South Africa - Dube, Mpumelelo (My University, 2021)
Mapping the location of Karoo dolerites is crucial for safe and efficient extraction of shale gas and groundwater exploration around the main Karoo Basin. To aid this mapping, a high-resolution airborne magnetic survey was conducted near Beaufort West in the Western Cape Province. This survey is a component of a five-year geoscientific research project by the Council for Geoscience. Dolerite sills and dykes, and other features, were mapped by filtering the magnetic data. Five lineament orientations associated with dolerite dykes, kimberlites, fractures and faults were mapped: E-W to ESE-WNW, NNW-SSE, NW-SE, NE-SW and NNE-SSW. The magnetic data mapped the extent of the hidden central parts of the sills in the dissected terrain. Sill boundaries are preferentially aligned NW-SE. Depth estimations were obtained for the magnetic sources using the Radial Averaged Power Spectrum technique and compared with SOEKOR seismic data along line BV21. Power spectrum transformation estimated depths to shallow magnetic sources of approximately 0.3 km or less. Intermediate sources are estimated to lie at depths between 3 km and 0.7 km. A 2D forward magnetic model was also generated over the seismic line. The model confirmed the inclined sheets connected to an inner sill, as mapped on the seismic data. The inner sill was mapped at ~ 1 km depth on the seismic data. This sill is part of the intermediate magnetic sources determined from the depth estimation technique. The mapped linear features were used to conduct a stress and strain analysis of the study area. Structural trends suggest that the principal compressive stress (σ1) direction related to the formation of the Cape Fold Belt and development of the Karoo sedimentary basin between ca. 300 and 215 Ma was N-S, but that it switched to NW-SE related to dextral strike-slip tectonics during Gondwana break-up between ca. 190 and 180 Ma. Post-rifting kimberlite dykes display predominant NNE to NE trends, suggesting that the principal extensional stress (σ1) occupied a NNE-SSW orientation. Kimberlite emplacement occurred during the Early Jurassic (170 Ma) to Mid-Cretaceous (80 Ma). This study shows that aeromagnetic surveys provide valuable complementary data for mapping the shape, size, depth and geometry of magnetic Karoo dolerites, thereby contributing evidence of the tectonic history in the Karoo basin
A research report submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Geosciences, University of the Witwatersrand, 2021